2011
DOI: 10.1093/annonc/mdq695
|View full text |Cite
|
Sign up to set email alerts
|

Male pattern baldness and the risk of prostate cancer

Abstract: This study shows an association between early-onset androgenic alopecia and the development of prostate cancer. Whether this population can benefit from routine prostate cancer screening or systematic use of 5-alpha reductase inhibitors as primary prevention remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
3
46
1
1
Order By: Relevance
“…A number of studies have found no association between androgenetic alopecia and prostate cancer (9)(10)(11)15) or suggestive evidence of an increased risk of prostate cancer (12), others have found androgenetic alopecia to be associated with an increased risk of prostate cancer (13,14,18), whereas 2 recent studies have found androgenetic alopecia to be associated with a decreased risk of prostate cancer (16,17). While differences in sample size, study design, and exposure assessment might plausibly explain much of the inconsistency between studies, the direction of estimated associations has differed even among those studies that assessed androgenetic alopecia at specific reference ages using an adapted Hamilton-Norwood scale (16)(17)(18). One such case-control study found a 2-fold higher relative odds of prostate cancer in men with any androgenetic alopecia at age 20 years (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have found no association between androgenetic alopecia and prostate cancer (9)(10)(11)15) or suggestive evidence of an increased risk of prostate cancer (12), others have found androgenetic alopecia to be associated with an increased risk of prostate cancer (13,14,18), whereas 2 recent studies have found androgenetic alopecia to be associated with a decreased risk of prostate cancer (16,17). While differences in sample size, study design, and exposure assessment might plausibly explain much of the inconsistency between studies, the direction of estimated associations has differed even among those studies that assessed androgenetic alopecia at specific reference ages using an adapted Hamilton-Norwood scale (16)(17)(18). One such case-control study found a 2-fold higher relative odds of prostate cancer in men with any androgenetic alopecia at age 20 years (18).…”
Section: Discussionmentioning
confidence: 99%
“…While differences in sample size, study design, and exposure assessment might plausibly explain much of the inconsistency between studies, the direction of estimated associations has differed even among those studies that assessed androgenetic alopecia at specific reference ages using an adapted Hamilton-Norwood scale (16)(17)(18). One such case-control study found a 2-fold higher relative odds of prostate cancer in men with any androgenetic alopecia at age 20 years (18). Another case-control study, which assessed androgenetic alopecia at age 30 years, found a 29% reduction in the odds of prostate cancer for men with any androgenetic alopecia, and a stronger reduction in when considering only men older than 60 years at interview (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Some studies suggested a relationship between PCa and baldness in a positive 13 or inverse 14 relationship, although some suggested no relation at all. 15 Aging and androgens are known risk factors for both PCa and MPB, with androgens implicated in the development of both conditions.…”
Section: Discussionmentioning
confidence: 99%